Base de información y modelo de evaluación de Calidad de hábitat con el sistema de Valoración integrada de servicios y compensaciones de ecosistemas (InVEST) en la cuenca del río Isinche de la provincia de Cotopaxi 2020-2021 - Simaluisa Chasi, Tania Elizabeth (2021)
The present research work is oriented to obtain a model for the evaluation of habitat quality with the integrated valuation system of ecosystem services and compensations, in this way it was possible to make a reference to the study area in the Isinche River basin, located in the province of Cotopaxi in the cantons of Pujilí and Latacunga. Biodiversity is linked to ecosystems that can be estimated in the land, using maps together with habitat and species threats. The assessment by means of InVEST software was applied to the model investigated, which yielded four important factors, namely: the relative impact of each threat, the relative sensitivity of each type of habitat, the distance between the inhabitants and the sources of threat and the degree of legal protection of the territory. The InVEST software model made it possible to map in raster the digital elevation (DEM) of the Isinche river basin. The method employed consisted of a qualitative process oriented to the operation of the habitat quality modeling and habitat derogation, the procurement of information and input and output files by means of a bibliographic review of previous studies to generate the maps of ecosystem services. This land use land cover map is used for threat and sensitivity data to be connected through the code that helps to define the land classification to which it belongs and in turn is classified as habitat and non-habitat, where zero is the value to define a "non-habitat" and one for "habitat". The InVEST software analyzed the database using mathematical algorithms defined for the variables required in the habitat quality balance, and defined which variable is used for the derogation that is automatically simulated in the output folder provided by the program.